1999
DOI: 10.1099/0022-1317-80-5-1147
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in cells infected with bovine viral diarrhoea virus: a crucial step in the induction of apoptosis.

Abstract: Bovine viral diarrhoea virus (BVDV) belongs to the genus Pestivirus of the family Flaviviridae. Both a noncytopathic (ncp) and an antigenically related cytopathic (cp) BVDV can be isolated from persistently infected animals suffering from mucosal disease. In every case studied so far, the genomic changes leading to the cp biotype correlate with the production of the NS3 nonstructural protein, which, in the ncp biotype, is present in its uncleaved form, NS23. This report shows that, in contrast to ncp BVDV, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 57 publications
5
89
0
Order By: Relevance
“…In addition, oxydative stress [40], intracellular viral RNA accumulation [44], caspase-12-associated ER stress [18], and mitochondriadependent caspase-9 activation [11] have been reported to be associated with cp BVDV-induced apoptosis. Here we show that NS3/NS3∆50 of BVDV induced apoptosis, and correlated with both caspase-8 and caspase-9 activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, oxydative stress [40], intracellular viral RNA accumulation [44], caspase-12-associated ER stress [18], and mitochondriadependent caspase-9 activation [11] have been reported to be associated with cp BVDV-induced apoptosis. Here we show that NS3/NS3∆50 of BVDV induced apoptosis, and correlated with both caspase-8 and caspase-9 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NS3/ NS3∆50 protein induces caspase-8-and -9-dependent apoptosis, several lines of evidence suggest that several factors (cellular and/or viral) or activation pathways of apoptosis are likely to be involved in the BVDV-associated apoptosis process. The facts that oxidative stress is observed in cells infected with cp BVDV [40], and that caspase-12-associated ER stress, a feature that was not addressed in this study, is observed in cp BVDV-induced apoptosis are consistent with the latter statement [18]. Caspase-12, which resides within the cytoplasmic side of the ER, is believed to play a central role in the ER stress-mediated apoptosis [31] and can activate caspase-8 [7] which in turn stimulates, through Bid processing, cytochrome c release and activates caspase-9 [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,31 Similarly, it has been shown that TNF-a is released by primary bovine fetal muscle cells experimentally infected with cp BVDV, and this might be involved in caspase-8 activation, albeit the effect was rather small compared with the strong stimulation of caspase-3 activity. 48 In other studies, oxidative stress, 36 endoplasmic reticulum (ER) stress, 19,27 intracellular viral RNA 42 or double-stranded (ds) RNA accumulation, 47 and mitochondria-dependent caspase-9 activation 13 have been reported to be associated with cp BVDVinduced apoptosis.…”
mentioning
confidence: 99%
“…27,33 It has been previously reported that cell death associated with cp BVDV in vitro is mediated by apoptosis. 15,17,36,50 Infection of cell cultures with BVDV of the cp biotype is characterized by the predominant expression of the NS3 protein, the cleaved form of the nonstructural protein NS2-3. In contrast, in cells infected with ncp BVD viruses, the uncleaved NS2-3 precursor protein prevails.…”
mentioning
confidence: 99%